Position of a Single Judge in a Small Claim Court: Role and Responsibilities - Henny Saida Flora; Ning Adiasih; Selamat Lumban Gaol; Indriyana Dwi Mustikarini; Johannes Johny Koynja (Inovasi Pratama Internasional. Ltd, 2024)
In the context of litigation, a simple lawsuit is one that has no legal recourse. It is an objection that is heard by judges who are senior in the field. This type of lawsuit is convenient for the community at large, encompassing companies, People's banks, and other banks whose proof is simple. The data collection methods employed in this research are observation, interview, and documentation. The subject of this research is the application of a straightforward lawsuit in the Jakarta District Court, specifically, the types of cases that may be resolved by such a suit. This is a qualitative study employing an empirical juridical approach, employing a descriptive methodology. This research provides a conclusion that a simple lawsuit based on Supreme Court Regulation Number 4 of 2019 represents a significant advancement over Supreme Court Regulation Number 2 of 2015. However, it was subsequently amended by Supreme Court Regulation Number 4 of 2019. The value of the lawsuit is set at IDR 500,000,000.00, with a case subscription period of 25 days. The categories of this simple lawsuit are default (breach of promise) and tort, with the exception of those concerning land issues. The application of this simple lawsuit at the Pekanbaru District Court is commendable, although a few obstacles remain. However, these do not impede the resolution of existing cases. With regard to the obstacles for judges in this simple lawsuit, namely the District Court, it is necessary to implement a more extensive socialization program to educate the public about this simple lawsuit. This will help to prevent any errors when filing a case resolved through a simple lawsuit.